Analysis of Factors Affecting the Income of Vaname Shrimp Farming Businesses (Litopenaeus vannamei) in Parigi District, Pangandaran Regency - Ika Ayu Lestari; Ine Maulina; Nora Akbarsyah; Asep Agus Handaka Suryana (Grouper, 2026)
Vaname shrimp (Litopenaeus vannamei) farming is a highly profitable fishery business with the potential to increase farmers' income. This study aims to analyze the income from vaname shrimp farming in Parigi Subdistrict, Pangandaran Regency, and to analyze the factors that affect the income from this farming business. The study used a survey method with a quantitative approach. Data collection was conducted through observation, interviews, and questionnaires with vaname shrimp farmers. Data analysis was performed descriptively to describe the characteristics of the pond farming system, as well as quantitatively using cost and income analysis and multiple linear regression analysis. The results showed that the farming systems used consisted of semi-intensive, intensive, and super-intensive systems with differences in pond area, pond construction, number of water wheels, and stocking density. Business vaname shrimp farming provides profits in each farming system, with an average income per production cycle in semi-intensive ponds of IDR 92,820,000–IDR 201,874,333, intensive ponds of IDR 614,910,492, and super-intensive ponds of IDR 920,702,000. The regression analysis results show that the selling price variable has a significant effect on the income of vaname shrimp farming businesses, while probiotic costs and labor costs do not have a significant effect on income. The research conclusion shows that vaname shrimp farming businesses in Parigi Subdistrict are profitable in every farming system, and the selling price is the factor that has the most significant effect on income.